2022
DOI: 10.1093/molbev/msac066
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Assembly of 20 Chicken Genomes Reveals the Undetectable Phenomenon for Thousands of Core Genes on Microchromosomes and Subtelomeric Regions

Abstract: The gene numbers and evolutionary rates of birds were assumed to be much lower than those of mammals, which is in sharp contrast to the huge species number and morphological diversity of birds. It is therefore necessary to construct a complete avian genome and analyze its evolution. We constructed a chicken pan-genome from 20 de novo assembled genomes with high sequencing depth, and identified 1,335 protein-coding genes and 3,011 long noncoding RNAs not found in GRCg6a. The majority of these novel genes were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 87 publications
(104 reference statements)
3
49
1
Order By: Relevance
“…The publication of the chicken genome (Red junglefowl) in 2004 paved the way for understanding the genetic basis for distinguishing the different phenotypes of domesticated chickens from their wild relatives (K. 1, 2004). Recent studies using population resequencing data and de novo assembled-based chicken pan-genome have improved the sequencing quality for the assembly of complete avian genomes and revealed that the numbers of chicken genes are comparable to those of other tetrapod vertebrates and a new pan-genome pattern of birds (Li et al, 2022; Wang et al, 2021). In addition to pan-genome analyses, transcriptome annotation is crucial for a wide array of biological research areas (Cunningham et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The publication of the chicken genome (Red junglefowl) in 2004 paved the way for understanding the genetic basis for distinguishing the different phenotypes of domesticated chickens from their wild relatives (K. 1, 2004). Recent studies using population resequencing data and de novo assembled-based chicken pan-genome have improved the sequencing quality for the assembly of complete avian genomes and revealed that the numbers of chicken genes are comparable to those of other tetrapod vertebrates and a new pan-genome pattern of birds (Li et al, 2022; Wang et al, 2021). In addition to pan-genome analyses, transcriptome annotation is crucial for a wide array of biological research areas (Cunningham et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we compared our 1,420 new genes with the 1,335 new genes recently found in 20 chicken genomes 11 . As shown in Figure 4f, our new genes with a mean length of 7,008 bp are much longer than the 1,335 new genes with a mean length of only 1,413 bp.…”
Section: New Protein-coding Genes Are Found In Indigenous Chicken Gen...mentioning
confidence: 99%
“…Moreover, hundreds of indigenous and commercial chicken breeds from all over the world have been resequenced using short-reads sequencing technologies 10 . Recently, Li, et al have assembled a pangenome for chicken using short reads, long reads and Hi-C data 11 . With a contig N50 of 5.89~16.72 Mb and a complete BUSCO 12 value of 92.4%~95.3% for a pan-genome, this assembly prevents the identi cation of the subtle differences in gene compositions of the chickens.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Warren et al (2017) added an additional 183 Mb sequences and assembled chromosomes 30-33 for the chicken reference genome. To fill the gaps of the chicken reference genome, recently two pangenomes were built that reported additional sequences absent from the GRCg6a reference genome (Wang K. et al, 2021;Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%